UJI DENSITAS DAN POROSITAS SERTA KARAKTERISASI BATU ANDESIT LETUSAN GUNUNG SEMERU DI DESA SUMBERULUH KECAMATAN CANDIPURO KABUPATEN LUMAJANG - Rohmah, Nofia; Yushardi, Yushardi; Sudarti, Sudarti (LPPM UNIVERSITAS PGRI SILAMPARI, 2023)
Density and porosity tests are used to test and determine the quality of andesite stone resulting from the eruption of Mount Semeru. Andesite stone is used as an asphalt mixture in the PG Jatiroto area. The easy collapse of the asphalt road is the main factor of this research. The results of the density and porosity tests that have been carried out show quite good results. Where the results of the density test are in accordance with the indicator values ​​on igneous rock. This means that the stone is sturdy enough to be used as an asphalt mixture. While the results of the andsit porosity test also showed good results. Therefore, these two tests can help researchers to find out the quality of the andesite stones used in the Jatiroto PG area. This andesite stone has a smooth texture. The size of the mineral grains is small and the distance is not too tight. The cavities are not too big so that there is still fluid to be absorbed into it.